Culturally conditioned aspects of the connotative meaning of precedent toponyms in the Belarusian and Slovak media discourse - Kazharnovich, Maryna P. (Journal of the Belarusian State University. Philology, 2019)
Modern media discourse makes extensive use of the connotative potential of a proper name for reflection, evaluation, and axiological interpretation of reality. Connotation includes meta-linguistic information that is relevant for understanding the meaning of onym when it is used in the secondary nomination. Hyper-nominativity of proper nouns is determined by the presence of a connotative meaning. The study implemented within the framework of this article is aimed at a comparative analysis of the connotative meaning of precedent toponyms in Belarusian and Slovak media discourse in order to identify the universal and culturally determined aspects of their functioning in metaphorical contexts. The article discusses the problem of determining the linguistic status of onym in the secondary nomination: traditional and modern approaches to solving this issue are highlighted. Special attention is paid to the theory of the connotative meaning of a proper name. The comparative analysis of toponymic connotonyms in Belarusian and Slovak media texts is descriptive and interpretative in nature and is aimed at identifying, describing and culturally interpreting the nationally determined aspects of the connotative meaning of case-related toponyms.